A multi-objective optimization of ballistic and cruise missile fire plans based on damage calculations from missile impacts on an airfield defended by an air defense artillery network. (April 2019) - Wade, Brian M
This paper presents a new methodology for optimizing missile fire plan parameters in order to maximize the damage caused to an airfield by the impacts of ballistic and cruise missiles that leak through an air defense artillery network using weaponeering calculations. This new methodology models the damage to the airfield runway, fuel infrastructure, and parked aircraft caused by both unitary and submunition warheads carried by the ballistic and cruise missiles. It then uses the airfield damage models paired with an air defense simulation in a multi-objective optimization to find the non-dominated frontier of missile fire plan parameters that inflict the greatest damage to the different parts of the defended airfield. It demonstrates the methodology for three increasingly sized ballistic and cruise missile fire plans.